Entrepreneurship challenge: A case study among single mother entrepreneurs in Northern Region - Abu, Noor Hidayah; Zainal Abidin, Faudziah; Ahmad Zaidi, Mohamad Faizal (2018)
Entrepreneurship is a vital route to economic growth for developed and developing country. Entrepreneurs are the main vehicle for entrepreneurship, contribute to employment, social, political stability, pioneer of innovation and competitive power.Besides, they become the main supplier of goods and services to a large industry.In Malaysia, women participation in entrepreneurship become increase included single mother entrepreneur.However, in reality not much is known about the challenges faced by them.Therefore, it is important to conduct research that focuses on single mother entrepreneurs.The main objective of this study was to fill the gap by exploring Malaysian single mother entrepreneurial in Northern region area personal challenges when conducting business. In this study, a qualitative method based on interviews was implemented.A total of 13 single mother entrepreneur respondents was selected.The results of the study revealed three main challenges that are faced by these single mother entrepreneurs in the northern region, which are difficulties in getting business assistance, operating in facilities which are incomplete and insufficient, and not enough exposure to social media which is capable of widening their product market.If these challenges are not rapidly overcome, it can have detrimental effects on these businesses.Therefore, the formulation of relevant governmental policy is important in assisting and further developing these single mother entrepreneurs and their businesses in the long run, in order to contribute toward the national economy.